Affective Communities : Anticolonial Thought, Fin-de-Siècle Radicalism, and the Politics of Friendship - Gandhi, Leela, 1966- (Book collections on Project MUSE., 2006)
Investigates friendships between anti-colonial Indians and anti-imperial 'westerners' in late-19th and early 20th centuries, claiming that such inter-cultural collaborations need to be added to annals of non-violent historiography.